Correlation between the insertion-deletion variant of the angiotensin-converting enzyme gene and various classes of heart failure: ACE gene polymorphism in heart failure - Tawfeeq, Rawaz D.; Ismael, Ava T.; Alwan, Mohammed H. (Cellular and Molecular Biology, 2023)
The angiotensin-converting enzyme (ACE) genetic variation for insertion/deletion (I/D) is located at the 16th intron of the ACE gene. A number of studies investigated the homozygous deletion genotype of ACE and its association with cardiovascular diseases. However, ACE’s genetic variation and its association with heart failure (HF) is yet to be confirmed. We examined the possibility of the association between the ACE I/D gene variant with the severity of HF. The ACE genotypes were determined by polymerase chain reactions using samples derived from 150 patients with HF and 90 healthy subjects which were age and gender-matched. These patients included those of all four of the New York Heart Association (NYHA) classes. Echocardiography was performed on all HF patients and ejection fraction (EF), left ventricular systolic and diastolic diameters were measured. The HF patients were redistributed to systolic where EF is equal and less than 45% and non-systolic HF where EF is more than 45%. We demonstrate a statistically significant difference in DD genotype in NYHA class IV in comparison to the control group. The values of odds ratio (OR) (95%CI) of the DD genotype (DD vs ID and II) were 3.37 (1.01-11.19) (p value = 0.039) and the OR (95%CI) of the D allele (D vs I) was 2.55 (0.98-6.65) (p value = 0.049). Higher frequencies of D allele compared to I allele is linked to severity of HF. DD variant of the ACE gene is associated with NYHA class IV heart failure. This could have a profound impact on risk stratification and prognosis of HF in the management of this condition.